Definition:Hyperbolic Cotangent

From ProofWiki
Jump to: navigation, search

Definition

Definition 1

The hyperbolic cotangent function is defined on the complex numbers as:

$\coth: X \to \C$:
$\forall z \in X: \coth z := \dfrac {e^z + e^{-z} } {e^z - e^{-z}}$

where:

$X = \set {z : z \in \C, \ e^z - e^{-z} \ne 0}$


Definition 2

The hyperbolic cotangent function is defined on the complex numbers as:

$\coth: X \to \C$:
$\forall z \in X: \coth z := \dfrac {\cosh z} {\sinh z}$

where:

$\sinh$ is the hyperbolic sine
$\cosh$ is the hyperbolic cosine
$X = \set {z : z \in \C, \ \sinh z \ne 0}$


Definition 3

The hyperbolic cotangent function is defined on the complex numbers as:

$\coth: X \to \C$:
$\forall z \in X: \coth z := \dfrac {e^{2 z} + 1} {e^{2 z} - 1}$

where:

$X = \left\{{z : z \in \C, \ e^{2 z} - 1 \ne 0}\right\}$


Also denoted as

  • The notation $\operatorname{cth} z$ is also found for $\coth z$.


Also see

  • Results about the hyperbolic cotangent function can be found here.


Sources